Bioactive Compounds From Coptidis Rhizoma Alleviate Pulmonary Arterial Hypertension by Inhibiting Pulmonary Artery Smooth Muscle Cells' Proliferation and Migration. Issue 2 (August 2021) - Luo, Shuai; Kan, Junyan; Zhang, Juan; Ye, Peng; Wang, Dongchen; Jiang, Xiaomin; Li, Minghui; Zhu, Linlin; Gu, Yue
Abstract : Abstract: Pulmonary arterial hypertension (PAH) is a devastating disorder characterized by excessive proliferation and vasoconstriction of small pulmonary artery vascular smooth muscle cells (PASMCs). Coptidis rhizoma (CR) because of the complexity of the components, the underlying pharmacological role and mechanism of it on PAH remains unknown. In this article, the network pharmacological analysis was used to screen the main active constituents of CR and the molecular targets that these constituents act on. Then, we evaluated the importance of berberine and quercetin (biologically active components of CR) on the proliferation and migration of PASMCs and vascular remodeling in experimental models of PAH. Our results showed that berberine and quercetin effectively inhibited the proliferation and migration of hypoxia-induced PASMCs in a manner likely to be mediated by the suppression of MAPK1, NADPH oxidase 4 (NOX4), and cytochrome P450 1B1 (CYP1B1) expression. Furthermore, berberine and quercetin treatment attenuates pulmonary hypertension, reduces right ventricular hypertrophy, and improves pulmonary artery remodeling in monocrotaline-induced pulmonary hypertension in rat models. In conclusion, this research demonstrates CR might be a promising treatment option for PAH, and the network pharmacology approach can be an effective tool to reveal the potential mechanisms of Chinese herbal medicine.